Komik Mbak Pia: Representasi Budaya Organisasi Badan Pusat Statistik Melalui Komunikasi Visual - Saleh, Andri; Setianti, Yanti; Budiana, Heru Ryanto (ULTIMART Jurnal Komunikasi Visual, 2023)
Mbak Pia’s comic is a comic strip aired in Varia Statistik magazine, an internal magazine that published monthly within the Statistics Indonesia (BPS). Since it was first aired in 2012, Mbak Pia's comic has now reached its 117th series. Mbak Pia's comic depicts the world of daily work of BPS employees packaged in a funny and entertaining story. But on the other hand, this comic also conveys an important message in the form of internalizing core values in the BPS organization: professional, integrity, and trustworthy. The purpose of this study was to analyze the message conveyed in the Mbak Pia’s comic. The method used is an interpretive method with a qualitative approach. While the analysis used is the semiotic analysis of Roland Barthes. The results of this study show that Mbak Pia's comics not only tell about the world of daily work of BPS employees and internalization of core values in the BPS organization, but are also loaded with criticism of work culture that is not in accordance with the core values of the BPS organization. Some of the things that are criticized in the comic story are those related to planning, employee performance, and employee competence. For this reason, BPS needs to emphasize a strong commitment to all its employees in upholding the core values of the BPS organization. Keywords: comics; culture; organization; visual communication